Efficient conversion of chitin biomass into 5-hydroxymethylfurfural over metal salts catalysts in dimethyl sulfoxide -water mixture under hydrothermal conditions. (December 2016) - Yu, Songbai; Zang, Hongjun; Chen, Song; Jiang, Yi; Yan, Bing; Cheng, Bowen
Abstract: The direct conversion of chitin biomass to 5-hydroxymethylfurfural (5-HMF) over metal salts catalysts was studied systemically in a dimethyl sulfoxide -water solvent mixture under hydrothermal conditions. N -acetyl-d -glucosamine (GlcNAc) was chosen as model substrate to investigate the reaction. Sixteen catalysts were investigated, and FeCl2 exhibited the best performance –achieving 5-HMF with yields of 26.6% and 37.9% from chitosan and GlcNAc, respectively, at 180 °C under hydrothermal conditions. These are the highest yields reported to date for 5-HMF obtained from chitosan and GlcNAc. Furthermore, the substrate scope was expanded from GlcNAc to various chitosan polymers with different molecular weights and chitin, 5-HMF yield from polymers were generally lower than that from GlcNAc.